2015
DOI: 10.1177/0954406215603741
|View full text |Cite
|
Sign up to set email alerts
|

A generalized semi-analytical load distribution model for clearance-fit, major-fit, minor-fit, and mismatched splines

Abstract: A generalized semi-analytical load distribution model for all common types of involute spline joints is proposed. It is formulated to model clearance-fit (side-fit) involute splines with contacts happening only at the drive flanks of the spline teeth, major or minor-diameter fit splines where additional contact occurs along the top land and the root land of the external spline teeth, respectively, as well as mismatched splines where an intentional lead mismatch is introduced to initiate contact along both driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…While the studies by Hong et al [1,[10][11][12] indicate that their proposed method is advantageous in capturing key effects and providing computationally efficient analyses, it lacks experimental validation; so do the other models cited previously. The literature contains several experimental studies on splined joints investigating surface wear and fatigue.…”
Section: Experimental Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…While the studies by Hong et al [1,[10][11][12] indicate that their proposed method is advantageous in capturing key effects and providing computationally efficient analyses, it lacks experimental validation; so do the other models cited previously. The literature contains several experimental studies on splined joints investigating surface wear and fatigue.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In Figure 1.1(b), a major-fit spline is shown with additional contact along the major diameter of the spline. Finally, in Figure 1.1(c), a minor-fit spline is shown that has additional contact along the minor diameter of the spline [1]. In major and minor diameter-fit splines, there is often a circumferential clearance such that the torque is carried by one side of the tooth flanks while the contact along the major or minor diameter centers the components.…”
Section: Background and Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Building on the results of their earlier FE study, Hong et al Benatar, Talbot and Kahraman, Journal of Advanced Mechanical Design, Systems, and Manufacturing, Vol.11, No.6 (2017) (2014b, 2015a, 2015b) published a family of semi-analytical models which both reduced the computational time immensely and surpassed the capabilities of the previous models which were mostly limited to purely torsional loading. These models captured the impact of loading type (purely torsional, spur, or helical gear loading) on the resultant load distribution of the joint for clearance-fit (Hong, et al, 2014a) as well as major and minor diameter-fit splines (Hong, et al, 2015a). The models also displayed the influence of index errors on the resultant load distributions of a splined joint (Hong et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%